THE LEGAL FRAMEWORK OF SHARIAH BANKING IN INDONESIA: IMPLICATIONS FOR FINANCIAL REGULATION AND MARKET DEVELOPMENT - Ahmad Narud; Rachel Chan; Nikhil Joshi (Yayasan Adra Karima Hubbi, 2025)
The rapid growth of Shariah banking in Indonesia has prompted significant regulatory developments to align financial practices with Islamic principles. However, the legal framework governing Shariah banking remains complex, raising questions about its effectiveness in fostering financial regulation and market development. This study examines the legal structure of Shariah banking in Indonesia, focusing on its implications for financial regulation and its role in promoting sustainable market growth. The research aims to identify gaps in the current legal framework and propose recommendations for enhancing regulatory coherence and market competitiveness. Using a qualitative approach, this study analyzes legal documents, regulatory policies, and secondary data from authoritative sources, complemented by interviews with key stakeholders in the Shariah banking sector. The findings reveal that while Indonesia has established a comprehensive legal framework for Shariah banking, challenges such as regulatory fragmentation, limited enforcement mechanisms, and insufficient integration with global Shariah standards persist. These issues hinder the sector's potential to contribute fully to financial inclusion and economic development. The study concludes that strengthening the legal framework through harmonized regulations, enhanced enforcement, and greater alignment with international Shariah standards is crucial for the sustainable growth of Shariah banking in Indonesia.